Modeling the Temporal Variability in Saturn's Magnetotail Current Sheet From the Cassini F‐ring Orbits. Issue 3 (5th March 2020) - Agiwal, O.; Hunt, G. J.; Dougherty, M. K.; Cowley, S. W. H.; Provan, G.
Abstract: The Cassini spacecraft completed 20 highly repeatable orbits during northern summer at Saturn, known as the F‐ring orbits, of which 18 are considered in this study. The spacecraft traversed Saturn's magnetotail current sheet during each apoapsis pass between 16 and 22 Saturn radii over 2‐day intervals and revealed a highly variable radial magnetic field from orbit to orbit. The solar wind and planetary period oscillations (PPOs) are significant sources of temporal variability in the Saturnian magnetosphere. PPOs refer to dual magnetic perturbation systems, one in each hemisphere, which have been observed to modulate the position and thickness of the magnetotail current sheet with a ∼ 10.7‐hr periodicity. Thus, we employ a model which considers dual‐modulation effects of the northern and southern PPO systems, together with a model of variable solar wind forcing on the magnetotail current sheet, to investigate their combined temporal effects on the radial magnetic field in the magnetotail. For all 18 F‐ring orbits considered, the modeled radial fields show excellent overall agreement with the temporal variability in the large‐scale structure of the observed radial fields (root mean square error < 1.5 nT for 80% of the orbits). The amplitudes of the northern PPO modulations are well constrained between 0.3 and 0.5 Saturn radii, and they exceed the southern modulations by a factor of 1.3. The solar wind forcing is observed to be highly variable from orbit to orbit. Key Points: A temporally variable magnetotail current sheet is observed at Saturn during the F‐ring apoapsis passes The variability can be explained by two rotating magnetic perturbation sources and variable solar wind forcing Results are consistent with a regime where the northern system is dominant with an amplitude ratio of ∼ 1.3